The Quest for Child-Friendly Carrier Materials Used in the 3D Semi-Solid Extrusion Printing of Medicines - Eveline E. M. van Kampen; Sejad Ayyoubi; Luc Willemsteijn; Kjeld J. C. van Bommel; Elisabeth J. Ruijgrok (MDPI AG, 2022)
This work gives a brief overview of carrier materials currently used in pharmaceutical studies on the three-dimensional (3D) semi-solid extrusion (SSE) printing of medicines for pediatrics. The suitability of using these carrier materials in pediatric formulations, concerning safety and toxicity, was reviewed by consulting the 'Safety & Toxicity of Excipients for Pediatrics' (STEP) database and the Food and Drug Administration (FDA) regulations. In the second part of this work, carrier materials were tested on their ability to form a semi-solid mixture with lactose by dual asymmetric centrifugation (DAC) and printing by SSE. With the combination of theoretical and experimental studies, this work will guide research toward grounded decision-making when it comes to carrier material selection for pharmaceutical pediatric 3D SSE printing formulations.